Positive solutions for a class of nonlocal impulsive BVPs via fixed point index - Infante, Gennaro; Pietramala, Paolamaria; Zima, Mirosława (Topological Methods in Nonlinear Analysis, 2010)
We study the existence of positive solutions for perturbed impulsive integral equations. Our setting is quite general and covers a wide class of impulsive boundary value problems. We also study other cases that can be treated in a similar manner. The main ingredient in our theory is the classical fixed point index theory for compact maps.